Micro- and nanoporous materials capable of absorbing solvents and oils reversibly: the state of the art - Acevedo Cortez, Javier Sebastián; Kharisov, Boris I.; Serrano Quezada, Thelma Elizabeth; Hernández García, Tomás Constantino (2016)
Abstract Treatment of petroleum spills and organic solvent pollution in general is an important issue; several techniques are under development to remove oil from water. The use of absorbents is one of the most common techniques to tackle this problem. These absorbents can be classiﬁed based on their characteristics of recyclability into irreversible and reversible ones. In this review, we discuss the application of several materials as oil absorbents, according to their classiﬁcation and characteristics such as hydrophobicity, surface area and oil absorption capacity. Also, the fabrication methods for some materials are presented and analyzed. Keywords Oil spills Composites Reversibility Aerogels Natural absorbents Micro- and nanoporous materials